The truth of metaphorical God-talk - Muis, Jan (Scottish journal of theology, 2010)
This article tries to show that metaphorical God-talk can be descriptive and true. First, it is established that true metaphorical descriptions of reality are possible. No special theory of ‘metaphorical truth’ is required for metaphorical descriptions. Next, it is argued that a realistic metaphorical description of God is possible because we can know the transcendent creator in the experience of being addressed by him in Jesus Christ. God-talk is an extension of our response to God's address. The truth-condition of metaphorical God-talk is God's self-revelation; its truth-criterion is biblical God-talk.